Digital Economy Empowers the Rural Revitalization of Hainan Free Trade Port - Take the Agricultural Development of Hainan Province as an Example - Lyu, Xuehai; Lyu, Wenbo (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
As agricultural development enters modernization, it has developed a high degree of innovation dependence on the digital economy model. The digital economy has the advantages of fast channels, extremely fast sales, convenient transportation, and efficient inventory, which has enabled agricultural output and demand to reach a new high level of balance. Taking the agricultural development in Hainan Province as an example, this paper empirically studies the enabling mechanism and effect of the digital economy model on the agricultural economy.